Pengaruh Variasi Waktu Milling terhadap Temperatur Nano komposit Fe3O4-MgH2 sebagai bahan baku katalis pada Tabung Hydrogen Storage - Maulinda; TM Zulfikar; ZulkarnainJalil; Adi Rahwanto; Ismet (Jurnal Serambi Engineering, 2024)
Metal materials can be used in renewable energy with future technologies for safe hydrogen storage media. Metal hydrides are a safe and effective way to store hydrogen for vehicle applications. Due to its high capacity in mass and volume for hydrogen storage, metal hydrides are currently the subject of intense research. However, the thermodynamic properties of magnesium hydride (MgH2) produce moderate temperatures, during the hydrogen desorption reaction reaching about 3000C to 4150C at 1 bar. The thermodynamic properties of high MgH2 cause the desorption temperature to also increase. The enthalpy produces high desorption (about 74 KJ/mol H2). In addition, the process of transforming magnesium into magnesium hydride takes a long time, (for 60 hours). From the results of the study, iron sand, a material from nature, which has been extracted into Fe3O4 powder, is used as a catalyst. This is done to improve the absorption properties and reaction kinetics of hydrogen storage materials based on MgH2, namely magnetite Fe3O4. The yield of Magnetite Extraction (Fe3O4) from iron sand is 85% purity, compared to the purity of Iron sand before extraction, which is 81%. Mechanical alloying methods are used to process MgH2-Fe3O4 samples, with different milling times and different catalysts.